Cartoon in advertising: Kiko da Silva’s campaign for Dental Association of Pontevedra and Ourense. When an advertising campaign is information of social interest - Caballero Wangüemert, Félix; Román Portas, Mercedes (Estudios sobre el Mensaje Periodístico, 2019)
Despite the growing use of humor in advertising, cartoon is not yet common. This article analyzes the campaign that Galician artist Kiko da Silva made for the Dental Association of Pontevedra and Ourense in 2015 to warn population of potential risks of new dental franchised clinics and to promote to «lifelong» dentists as an alternative. We have reviewed some of the literature on humor in advertising, analyzed the two campaign ads and interviewed both the humorist who executed it as advertisers who designed it. It has been concluded that the strips helped to fix the readers’ attention and to make them to reflect on the subject.
Keywords: Cartoon; advertising; information; Kiko da Silva; Galicia.